58.4k views
3 votes
Find (f + g)(y).
f(y) = 1/y
g(y)= y2+2y-5

2 Answers

0 votes

For this case we have given two functions f (y) and g (y), then:


(f + g) (y) = f (y) + g (y)

We have:


f (y) = \frac {1} {y}\\g (y) = y ^ 2 + 2y-5

Adding we have:


(f + g) (y) = \frac {1} {y} + y ^ 2 + 2y-5

Finally:


(f + g) (y) = y ^ 2 + \frac {1} {y} + 2y-5

Answer:


(f + g) (y) = y ^ 2 + \frac {1} {y} + 2y-5

User Anil Vishnoi
by
5.2k points
2 votes

Answer:

(f+g)(y) = 1/y + y2+2y-5

Explanation:

To find (f+g)(y) we literally add the two expressions together. The expression becomes:

(f+g)(y) = f(y) + g(y)

= 1/y + y2+2y-5

User Mark Thistle
by
5.1k points